Penataan Objek Wisata Air Terjun Ngamba Mbu’u Di Desa Tonggo Papa Kecamatan Ende Kabupaten Ende (Dengan Pendekatan Arsitektur Ekologis) - Papa, Yohanes De Deo; Mochdar, Dian Fitriawati; Mbuu, Alfons (TEKNOSIAR, 2022)
One of the natural attractions of Ende Regency which is currently starting to appear and bearranged is Ngamba Mbu'u Waterfall, as one of the natural attractions in Tonggo Papa Village, EndeDistrict, Ende Regency, NTT Province. The Ngamba Mbu'u Waterfall Tourism Object has great potential tobe reorganized. However, this high potential is still not supported, where the number of visitors to theNgamba Mbu'u Waterfall Tourism Object is increasing and the provision of tourism objects, both facilitiesand infrastructure is not optimal.The method used is an architectural design method with the concept of Ecological Architecture as a design reference. The analysis used in this design includes environmental analysis, actor analysis, spatialanalysis, shape analysis and outdoor space analysis.The results obtained from the design of the Ngamba Mbu'u waterfall attraction in Tonggo Papa Village refer to the Ecological Architecture Concept as a design reference, namely by utilizing the landaround the waterfall tourist attraction to attract tourists' attention for recreation and bathing in the waterfallpool. The facilities that will be built at the tourist attraction are parking lots, lopo-lopo, managementbuildings, wooden bridges, and recreational facilities.